Robotic liver resection for hepatocellular carcinoma: A systematic review. Issue 4 (28th May 2019) - Magistri, Paolo; Tarantino, Giuseppe; Assirati, Giacomo; Olivieri, Tiziana; Catellani, Barbara; Guerrini, Gian Piero; Ballarin, Roberto; Di Benedetto, Fabrizio
Abstract: Background: Hepatocellular carcinoma (HCC) represents a leading cause of death in patients with cirrhosis. This review attempts to clarify the role of robotic surgery for HCC in terms of oncologic outcomes. Materials and methods: A systematic literature search was performed according to the PRISMA statement including papers comparing open, robotic, and laparoscopic approach for liver surgery. If more than one study was reported by the same institute, only the most recent or the highest quality study was included. Results: The literature search yielded 302 articles; titles and abstracts were reviewed for inclusion. Ten papers were finally included in this review for a total of 307 patients who underwent robotic resection for HCC. Conclusions: Robotic liver resection for HCC is effective in terms of oncological results as compared with open and laparoscopic approach when performed in experienced centers and is accurate in terms of R0 rates and disease‐free surgical margin.